Peningkatan Kompetensi Kader Kesehatan Dalam Pemantauan Pertumbuhan Balita Berbasis Pengukuran Antropometri di Kabupaten Sitaro - Yulianty Sanggelorang; Jainer Pasca Siampa; Irny Evita Maino; F. Ari Anggraini Sebayang (Universitas Muhammadiyah Malang, 2026)
Purpose – To evaluate the effectiveness of a standardized anthropometry training program for Posyandu cadres in Dame I Village, Sitaro Regency, in improving knowledge and procedural compliance for anthropometric measurement and the classification of nutritional status among children under five. Design/methodology/approach – This Community Engagement Program employed a pre–post design without a comparison group. The intervention comprised didactic sessions, a work leaflet, instructor-led demonstrations, and guided practice. Knowledge was assessed immediately before and after training using a structured questionnaire; the Shapiro–Wilk test was applied to examine normality and pre–post differences were analyzed with the Wilcoxon signed-rank test. Skills were evaluated through direct observation of compliance with a 22-item checklist (preparation, weighing, length/height measurement, documentation, and interpretation of anthropometric indices). Participants were all available health cadres (n=10). Findings – Mean knowledge scores increased by 2.80 points (pre: 12.10 ± 1.663; post: 14.90 ± 0.316), yielding a statistically significant difference (p = 0.005) in bivariate analysis. All participants met 22/22 items on the procedural compliance checklist during the evaluation of anthropometric practice. These outcomes indicate improvements in cognitive and psychomotor capacities relevant to accurate anthropometric measurement and the classification of child nutritional status. Originality/value – The program emphasizes comprehensive standardization of anthropometric measurement in an island setting by integrating practical quality-assurance components (pocket SOP/leaflet, checklist, and an agenda for inter-rater alignment) into a single training package. The demonstrated, significant gains in knowledge and 100% procedural compliance underscore capacity building for cadres as a critical lever to improve nutrition data quality and accelerate early detection of stunting at the community level.